2008
DOI: 10.1002/bdra.20481
|View full text |Cite
|
Sign up to set email alerts
|

Unique spatial and cellular expression patterns of Hoxa5, Hoxb4, and Hoxb6 proteins in normal developing murine lung are modified in pulmonary hypoplasia

Abstract: Background-Hox transcription factors modulate signaling pathways controlling organ morphogenesis and maintain cell fate and differentiation in adults. Retinoid signaling, key in regulating Hox expression, is altered in pulmonary hypoplasia. Information on pattern-specific expression of Hox proteins in normal lung development and in pulmonary hypoplasia is minimal. Our objective was to determine how pulmonary hypoplasia alters temporal, spatial and cellular expression of Hoxa5, Hoxb4 and Hoxb6 proteins compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 73 publications
(159 reference statements)
4
21
0
Order By: Relevance
“…Consistent with other studies in mouse and human lung, our results show that ␣ 2 -integrin is expressed in epithelia and adjacent mesenchyme of branching airway tips, whereas ␣ 3 -integrin is expressed in established airway branches (15,34,62). ␣ 2 ␤ 1 -integrin receptors are thought to promote mesenchymal-epithelial cell contacts as epithelial cells migrate into surrounding mesenchyme and associate with extracellular matrix binding partners and other cells (16,67).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with other studies in mouse and human lung, our results show that ␣ 2 -integrin is expressed in epithelia and adjacent mesenchyme of branching airway tips, whereas ␣ 3 -integrin is expressed in established airway branches (15,34,62). ␣ 2 ␤ 1 -integrin receptors are thought to promote mesenchymal-epithelial cell contacts as epithelial cells migrate into surrounding mesenchyme and associate with extracellular matrix binding partners and other cells (16,67).…”
Section: Discussionsupporting
confidence: 91%
“…A direct interaction between HoxB5 and E-cadherin is also less likely as E-cadherin is exclusively localized to epithelial cells (24,25). However, we and others have shown that certain Hox genes and divergent homeobox genes are localized to lung epithelial cells (22,32,42,43,61,62). We have not yet investigated the expression pattern of other Hox genes in BPS and CCAM, but it is possible that other Hox genes are aberrantly expressed in these lung lesions either independently of HoxB5 or through Hox gene auto-and cross-regulation, that might contribute to more direct Hox regulation of epithelial-expressed cell adhesion molecules in BPS and CCAM (6, 26, 44, 60, 68).…”
Section: Discussionmentioning
confidence: 92%
“…4). Furthermore, rodents treated with the RA inhibitor nitrofen, a common model of CDH-associated pulmonary hypoplasia, showed abnormal expression patterns of HOXA5 in the developing lung buds (55).…”
Section: Discussionmentioning
confidence: 99%
“…PSEN-1 and YAP expression were examined in whole lung sections from fetal mice of gestation E16, E17, and E18 in a modification of methods we have previously described [32]. Briefly, lungs were fixed in PBS (phosphate buffered saline) containing 4% PFA (paraformaldehyde), pH 7.2, for 4 hours and incubated in PBS with 30% sucrose overnight at 4°C.…”
Section: 0 Methods and Materialsmentioning
confidence: 99%